D. Malhadas, M.C.C. Dezotti e M.H. Moura Neves (coord.), Dicioná- rio grego-português, v. 1 (a-d), Cotia, Ateliê Ed., 2006, 264 p., ISBN 8574803278. - Brandão, Jacyntho Lins (Classica - Revista Brasileira de Estudos Clássicos, 2006)
MALHADAS, D.; DEZOTTI, M. C. C.; MOURA NEVES, M. H. (Coord.). Dicionário grego-português. Cotia: Ateliê Ed., 2006. v. 1 (a-d). 264 p., ISBN 8574803278.